From supramolecular chemistry to crystal engineering using hydrogen- and halogen bonds - Andree, Stefan Nirasher Lorenszo (Kansas State University, 2018)
A methodology for estimating hydrogen-bond preferences and binding affinities in solution, based on molecular electrostatic potential surfaces (MEPS), is presented using tritopic hydrogen bond acceptor and a series of aromatic carboxylic acids. The plot of calculated MEPS values against experimentally determined binding constants produces a goodness-of-fit of over 0.93 and a similar positive correlation is obtained between MEPS values and binding enthalpies. A series of tritopic N-heterocyclic compounds were synthesized and subjected to systematic co-crystallizations with selected multi-topic aliphatic and aromatic carboxylic acids to determine if ditopic and tritopic donors formulate assemblies with desired stoichiometries. The co-crystals formed contained the COOHᐧᐧᐧBzim synthon, and we observe vacant sites on the acceptor molecules. A series of co-crystallizations between tritopic N-heterocyclic compounds and perfluoroiodoarenes were carried to map out structural landscapes. At least one potential binding site on the acceptor is left vacant on all the four structures obtained. The absence of halogen bonds to all sites can be ascribed primarily due to deactivation of the σ-hole on the iodo-arene donors and partially due to steric hindrance. Four nonsteroidal anti-inflammatory (NSAID) drugs were chosen due to the presence of the COOH moiety, to establish if aqueous solubility can be modulated by systematic solubility measurements of the complex. Two different solids were obtained with a 1:1 and 1:3 stoichiometry. The solubility of the 1:1 co-crystal decreased by 12-fold compared to pure aspirin (3mg/mL at 20 °C) indicating that co-crystals can offer promising new solid forms of pharmaceutically relevant compounds. A series of hydrogen- and halogen bonding Tröger’s base derivatives were synthesized using aromatic N-heterocycles and the iodoethynyl functionality, followed by a series of co-crystallization between aliphatic dicarboxylic acids and symmetric ditopic acceptors. The results suggest that reducing the number of binding sites from three to two facilitates the formation of co-crystals with the desired stoichiometry. The results indicate that directed assembly can be achieved more easily when the molecular building blocks are conformationally rigid.
Keywords: Supramolecular chemistry; Hydrogen bonding; Halogen bonding; Crystal engineering; Tritopic acceptors; Tröger’s base